(untitled) (Physical Education, Health and Social Sciences, 2025)
Introduction: Artificial intelligence (AI) is revolutionizing nursing by enhancing clinical decision-making. AI-driven tools assist nurses in analyzing patient data, predicting outcomes, and improving care quality. This study explores AI’s role in nursing, highlighting its benefits, challenges, and impact on decision-making to enhance efficiency, accuracy, and patient safety in healthcare settings. Methodology: This quantitative study employed a cross-sectional design to assess the role of AI in nursing decision-making. A sample of 146 nurses was selected using a stratified random sampling technique. Data were collected through a structured questionnaire measuring AI-assisted decision-making efficiency, accuracy, and usability. Descriptive and inferential statistics were used for data analysis, including mean, standard deviation, and regression analysis. Ethical approval was obtained, and participant confidentiality was ensured throughout the study. Results: The study analyzed responses from 146 nurses, revealing that 78% found AI-assisted decision-making improved efficiency, while 82% reported enhanced accuracy in clinical judgments. AI integration reduced decision-making time by an average of 30%. Regression analysis showed a significant positive correlation between AI usage and decision accuracy (p < 0.05). However, 40% of participants expressed concerns about AI dependency. The findings suggest that AI positively impacts nursing decision-making, improving patient care while highlighting the need for proper training and integration strategies. Conclusion: The findings of this study support existing literature, emphasizing the positive impact of AI in nursing decision-making. However, concerns regarding AI’s reliability in complex cases and the need for structured AI training programs highlight areas requiring further exploration. Future research should focus on improving AI reliability and integrating AI-specific education into nursing curricula to enhance clinical decision-making and patient safety.